2017
DOI: 10.1002/ajmg.a.38460
|View full text |Cite
|
Sign up to set email alerts
|

Loss‐of‐function variants in NFIA provide further support that NFIA is a critical gene in 1p32‐p31 deletion syndrome: A four patient series

Abstract: The association between 1p32-p31 contiguous gene deletions and a distinct phenotype that includes anomalies of the corpus callosum, ventriculomegaly, developmental delay, seizures, and dysmorphic features has been long recognized and described. Recently, the observation of overlapping phenotypes in patients with chromosome translocations that disrupt NFIA (Nuclear factor I/A), a gene within this deleted region, and NFIA intragenic deletions has led to the hypothesis that NFIA is a critical gene within this reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…while the first case with a de novo NFIA point mutation was reported in 2012 as part of a series of children with autism spectrum disorder (Iossifov et al, 2012). To date, 15 individuals from nine unrelated families with genetic variants affecting solely NFIA have been reported with sufficient clinical data, to which we add two unreported individuals (Figure2; Supporting Information Table S2) (Revah-Politi et al, 2017). In six cases, the variant was found to have occurred de novo, four were familial with transmission of the variant from an affected parent, and in one case the segregation remained unclear (Mikhail et al, 2011).…”
Section: Nfiamentioning
confidence: 99%
See 1 more Smart Citation
“…while the first case with a de novo NFIA point mutation was reported in 2012 as part of a series of children with autism spectrum disorder (Iossifov et al, 2012). To date, 15 individuals from nine unrelated families with genetic variants affecting solely NFIA have been reported with sufficient clinical data, to which we add two unreported individuals (Figure2; Supporting Information Table S2) (Revah-Politi et al, 2017). In six cases, the variant was found to have occurred de novo, four were familial with transmission of the variant from an affected parent, and in one case the segregation remained unclear (Mikhail et al, 2011).…”
Section: Nfiamentioning
confidence: 99%
“…Several individuals have been reported with microdeletions involving NFIA and a variable number of flanking genes (C. P. Chen et al, 2011;Ji, Salamon, & Quintero-Rivera, 2014;Koehler et al, 2010;Labonne et al, 2016;Schirwani, Smith, & Balasubramanian, 2018), or with translocations in which additional genes on the translocated chromosome were disrupted or with position effects on other genes on either sides of the breakpoints of both chromosomes involved may have contributed to the phenotype (Lu et al, 2007;Shanske, Edelmann, Kardon, Gosset, & Levy, 2004). In other patients a single additional gene, such as PTEN or RBFOX1 (Revah-Politi et al, 2017;Zhao, 2013), was found to harbor a variant, which may have influenced the phenotype. Furthermore, four reported patients and two unpublished ones are known to us for whom insufficient clinical data were available to include them here (T. Attie-Bitach, G. Battista Ferrero and K. Devriendt, personal communications 2019) (Hollenbeck et al, 2017;Krumm et al, 2015).…”
Section: Nfiamentioning
confidence: 99%
“…Deletions of chromosome 1p32p31 (chromosome 1p32p31 deletion syndrome [MIM: 613735]) as well as deletions or sequence variants of NFIA lead to a phenotype with developmental delay, macrocephaly, ID, dysgenesis of the corpus callosum, ventriculomegaly or congenital hydrocephalus, and craniofacial dysmorphisms. [10][11][12][13][14][15][16][17][18][19] Haploinsufficiency of NFIX causes Sotos syndrome 2 or Malan syndrome (MIM: 614753), which is characterized by developmental delay, macrocephaly, ID, postnatal overgrowth, and mild craniofacial anomalies. [20][21][22][23][24][25][26] In addition, specific sequence variants affecting the 3 0 region of NFIX cause Marshall-Smith syndrome (MSS) (MIM: 602535), a more severe phenotype with severe intellectual disability, progressive dysostosis, respiratory difficulties, and a characteristic facial dysmorphism, and is presumably a result of a dominant-negative mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome is characterized by brain malformations and it can manifest or not renal urinary tract defects (OMIM #613735) 52 . The clinical presentation of the syndrome is highly variable and rarely all the described features are present in one individual 53 From the biological point of view, the gene-set enrichment analysis done with both lists of genes harboring PZM and germinal mutations showed a significant enrichment for several gene-sets previously involved in ASD pathogenesis: FMRP targets, genes involved in chromatin organization and high-confidence genes from SFARI 6 . Curiously, only the list of PZM genes showed a significant enrichment for genes targeted by miR-137.…”
Section: Nfia (Nuclear Factor I A)mentioning
confidence: 99%